AB0427 Comparative safety of abatacept vs tofacitinib in adults with moderate-to-severe ra: a systematic literature review and network meta-analysis. (12th June 2018) - Paul, D.; Diekemper, R.; Fazeli, M.; Husain, F.; Marshall, A.; Kuang, Y.; Curtice, T.
Abstract : Background: While targeted (biologic or synthetic) DMARDs are overall highly effective in improving symptoms and function in RA patients (pts), their comparative safety relative to each other remains inconclusive. Objectives: Compare the safety of abatacept (ABA) and tofacitinib (TOF) through a systematic literature review (SLR) and network meta-analyses (NMA). Methods: A comprehensive search of randomised and non-randomised clinical trials was conducted across MEDLINE, Embase and Cochrane CENTRAL databases from inception to June 2017. The PICO framework (population=moderate to severe RA pts; intervention=ABA and TOF; comparison=placebo and other RA therapies; outcome=AEs, treatment-related AEs [TrAEs], serious infections and treatment-related deaths) was used to design searches and define the eligibility of studies for inclusion. Additional searches were performed on relevant conference proceedings and the US clinical trials registry from the past 2 years (figure 1). Data configuration was performed by expert methodologists using DOC Data 2.0 (Doctor Evidence, Santa Monica, CA). NMAs using the random-effects model were used to examine the risk of AEs, TrAEs and serious infections in conventional DMARD-experienced ABA- and TOF-treated pts. Treatment-related death was not analysed in an NMA due to insufficient data. Results: Thirty-one randomised controlled trials (n=13, 978) were included for data extraction. Of these, ABA and TOF were examined in 16 and 15 trials, respectively. There were no head-to-head comparisons of ABA vs TOF. Most of the trial population were Caucasian (48%–98% across trials), had an average age ranging from 40 to 60 years and were predominantly female (60%–90%). Of the trials, 26 included a US population and 5 a non-US population. Out of 11 studies reporting treatment-related mortality, one study reported four deaths for pts on TOF 5 mg (n=321) within a 1 year follow-up. No such deaths were reported for ABA pts. The NMAs showed no significant differences in the risk of TrAEs for pts on TOF 5 or 10 mg compared with ABA with/without MTX (TOF 5 mg +MTX vs ABA+MTX: risk ratio [RR] 1.1, 95% CI: 0.77, 1.5; TOF 10 mg vs ABA: RR 1.1, 95% CI: 0.78, 1.6). These findings remained consistent for the risk of total AEs and serious infections. *One reference identified manually from a ClinicalTrials.gov record † Wrong publication date cut-off: meeting abstract published before 2015 Conclusions: Without head-to-head trials, the data available to make comparisons between abatacept and TOF are limited. Even after conducting an SLR and NMAs, precision is lacking in estimating differences. Additional studies, such as real-world observational analyses with larger patient samples and higher incidence of measured outcomes, are needed to further examine the safety differences of abatacept vs TOF. Disclosure of Interest: D. Paul Employee of: Bristol-Myers Squibb, R. Diekemper Grant/research support from: Bristol-Myers Squibb, Employee of: Doctor Evidence, M. Fazeli Grant/research support from: Bristol-Myers Squibb, Employee of: Doctor Evidence, F. Husain Grant/research support from: Bristol-Myers Squibb, Employee of: Doctor Evidence, A. Marshall Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Y. Kuang Grant/research support from: Bristol-Myers Squibb, Employee of: Doctor Evidence, T. Curtice Employee of: Bristol-Myers Squibb